Analysis of cost models and quantification models of customisation degree after VMI strategy implemented in different industries. (17th January 2013) - Wang, Shen-Tsu; Li, Meng-Hua
Enterprises often increase their inventory to satisfy unexpected demand increases, but the continuous increase of inventory costs weakens their future competitiveness. Thus, the vendor managed inventory (VMI) method was developed based on the interaction of credible information between the upstream and downstream manufacturers. This study aimed to integrate different inventory and cost models, correct and establish the current VMI decision mechanism, and construct two quantification models of customisation to provide a reference for the notebook computer and steel production industries for the implementation of VMI. The researched models can provide a comparison of the costs and degrees of quantified customisation of different industries before and after the implementation of VMI, and relevant policy data can serve as a decision reference for enterprises. The differences and similarities of different industries, as well as their management implications were discussed, which can provide a reference for related industries.